The award system [John Howard and John Hewson firing a cannon] - Pryor, Geoff, 1944- (1992)
The Oppisition is pushing for a low training wage. Many see this as an attack on the award system, and an indication that the Coalition, once in government, will set about de-regulating the labour market. -- Information provided be Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 8 July 1992.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Howard, John, -- 1939- -- Caricatures and cartoons; Hewson, John R. -- Caricatures and cartoons; Arbitration and award -- Australia -- Caricatures and cartoons; Wages -- Australia -- Caricatures and cartoons